Population infant hearing screening to intervention: Determinants of outcome from the parents' perspectives - Fitzpatrick, Elizabeth (University of Ottawa (Canada), 2007)
Background. Childhood hearing loss has a negative impact on healthy child development and is associated with poor outcomes in communication, social and academic development. Population-based infant hearing screening has received worldwide attention as an opportunity to improve developmental outcomes for children with hearing loss. Universal newborn hearing screening (UNHS) has become standard protocol in many countries and has recently been implemented in several Canadian provinces and territories. This study concerns population-based infant hearing screening and the potential benefits of this intervention for children and families. While there is evidence that screening can accurately identify babies with hearing loss before three months of age, less information is available on the effectiveness of early identification initiatives and how to maximize the potential opportunities provided by early detection of hearing loss. It is well recognized that UNHS must be part of an early hearing and communication development program. Objectives. The objectives of this thesis were to contribute to this developing field by: (1) exploring the effectiveness of infant hearing screening through traditional communication outcome measures, (2) identifying process and other outcomes that parents view as important benefits of early diagnosis of hearing loss, (3) examining parents' needs following identification of hearing loss, and (4) exploring parent preferences for service delivery following the diagnosis of hearing loss. Methods. Following a comprehensive review of the current state of knowledge, this study used combined quantitative and qualitative methodology approaches to examine these objectives through three interrelated inquiries: (1) an exploration of data from a prospective longitudinal study investigating the impact of early identification, (2) semi-structured interviews with parents whose children were diagnosed through screening and traditional referral routes and (3) a conjoint analysis survey to quantify parent preferences for service delivery. Conclusions and Implications for Practice and Policy. Applying a population health perspective, this research defined broader outcomes of early identification of childhood hearing loss from the perspective of families and highlighted contextual factors such as access to parent support and coordinated services, which may be important determinants of outcome to consider in program evaluation of screening initiatives. This study can inform the development and implementation of population hearing screening programs as they continue to grow across Canada and elsewhere. This project has the potential to impact health practice and policy by providing evidence-based direction for the delivery of services to young children with hearing loss and their families.
Keywords: Health Sciences, Audiology.; Health Sciences, Public Health.; Sociology, Individual and Family Studies.